2012
DOI: 10.3892/ijmm.2012.1102
|View full text |Cite
|
Sign up to set email alerts
|

Oxidative stress caused by a low concentration of hydrogen peroxide induces senescence-like changes in mouse gingival fibroblasts

Abstract: Periodontal tissue deteriorates under persistent oxidative stress induced by inflammatory reactions in the microflora of the oral cavity. This study aimed to evaluate the cellular properties of mouse gingival fibroblasts (MGFs) in the presence of oxidative stress. MGFs from 10-, 30- and 52-week-old mice were used to evaluate the changes in the cellular properties with aging. The study investigated the effects of oxidative stress on the cellular properties of MGFs from 10-week-old mice. The expression of p53, p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
47
0
2

Year Published

2013
2013
2022
2022

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 65 publications
(53 citation statements)
references
References 30 publications
4
47
0
2
Order By: Relevance
“…Previous works indicate that exogenous H 2 O 2 generates intracellular Ca 2+ signals and activation of transcription factors, including NFjB in rat nervous cells and human dermal fibroblasts; however, a high variability of responses has been reported according to cell type (23)(24)(25). Accordingly, H 2 O 2 induced Ca 2+ -dependent signaling at concentrations similar to this study in osteoclast-like cells (5), whereas concentrations from 20 lM induced senescence of gingival fibroblasts from mice (26).…”
Section: Discussionsupporting
confidence: 65%
“…Previous works indicate that exogenous H 2 O 2 generates intracellular Ca 2+ signals and activation of transcription factors, including NFjB in rat nervous cells and human dermal fibroblasts; however, a high variability of responses has been reported according to cell type (23)(24)(25). Accordingly, H 2 O 2 induced Ca 2+ -dependent signaling at concentrations similar to this study in osteoclast-like cells (5), whereas concentrations from 20 lM induced senescence of gingival fibroblasts from mice (26).…”
Section: Discussionsupporting
confidence: 65%
“…Gingival fibroblasts are known to be affected by H 2 O 2 . 32,33 However, studies have shown that fibroblasts in other parts of the body are more strongly affected. 34 In the present study, highly concentrated H 2 O 2 caused inflammation in gingival fibroblasts and had toxic effects, with marked changes in cell morphology.…”
Section: Discussionmentioning
confidence: 99%
“…2,3 Recently, studies have pointed to oxidative stress as being part of the pathogenesis of periodontal diseases. 4 Oxidative stress is a condition caused by a harmful increase in the production of reactive oxygen species (ROS), 5 which are important signalling molecules in the regulation of several cellular processes, 6 emerging when there is an imbalance between ROS levels and the host antioxidant defences. Consequences of the oxidative stress include adaptation, damage or cell death 7 through a variety of mechanisms, such as DNA, lipid and protein damage.…”
Section: Introductionmentioning
confidence: 99%